The Voices of Typers: Examining the Educational Experiences of Individuals Who Use Facilitated Communication - McKee, Aja; Gomez, Audri Sandoval (Disability Studies Quarterly, 2020)
As the number of students with autism grows, professionals must find ways to understand how to best educate this student population. Although current research addresses teaching students with autism, studies on educating autistic students with limited or unreliable verbal speech is nominal. In this qualitative study, interviews with eight autistics who type using the method facilitated communication are analyzed in relation to their educational experiences. The study resulted in a number of key findings that play significant roles in the participants' educational experiences, including (a) the notion of disability hierarchy and the presumption of competence, (b) the importance of building relationships and the perceptions of friendship, (c) developing a sensory friendly environment, and (d) understanding behavior and body movement. Results suggest that the educational needs of these students must be reexamined. Teachers must establish a deeper understanding of the disability and develop innovative practices to best meet the needs of autistic students with limited or unreliable verbal speech in their classrooms.